The Cambridge companion to Jewish American literature - Wirth-Nesher, Hana (2003)
Introduction:Jewish American literatures in the making /Hana Wirth-Nesher,Michael P. Kramer –Beginnings and ends: the origins of Jewish American literary history /Michael P. Kramer –Imagining Judaism in America /Susannah Heschel –Of crucibles and grandfathers: the East European immigrants /Priscilla Wald –Coney Island, USA: America in the Yiddish literary imagination /David G. Roskies –Hebrew literature in America /Alan Mintz –Traces of the past: multilingual Jewish American writing /Hana Wirth-Nesher –Accents of the future: Jewish American popular culture /Donald Weber –Jewish American poetry /Maeera Y. Shreiber –Jewish American writers on the left /Alan Wald –Jewish American Renaissance /Ruth R. Wisse –Holocaust and the Jewish American imagination /Emily Miller Budick –Jewish American women writers and the race question /Susan Gubar –On contemporary literary theory and Jewish American poetics /Shira Wolosky –Identity matters: contemporary Jewish American writing /Tresa Grauer.